Carbon Nanotubes Modified by Venturello Complex as Highly Efficient Catalysts for Alkene and Thioethers Oxidation With Hydrogen Peroxide - Evtushok, Vasiliy Yu; Ivanchikova, Irina D.; Podyacheva, Olga Yu; Stonkus, Olga A.; Suboch, Arina N.; Chesalov, Yuri A.; Zalomaeva, Olga V.; Kholdeeva, Oxana A. (Frontiers in Chemistry, 2019)
In this work, we elaborated heterogeneous catalysts on the basis of the Venturello complex [PO4{WO(O2)2}4]3- (PW4) and nitrogen-free or nitrogen-doped carbon nanotubes (CNTs or N-CNTs) for epoxidation of alkenes and sulfoxidation of thioethers with aqueous hydrogen peroxide. Catalysts PW4/CNTs and PW4/N-CNTs (1.8 at. % N) containing 5-15 wt. % of PW4 and differing in acidity have been prepared and characterized by elemental analysis, N2 adsorption, IR spectroscopy, HR-TEM, and HAADF-STEM. Studies by STEM in HAADF mode revealed a quasi-molecular dispersion of PW4 on the surface of CNTs. The addition of acid during the immobilization is not obligatory to ensure site-isolation and strong binding of PW4 on the surface of CNTs, but it allows one to increase the PW4 loading and affects catalytic activity and product selectivity. Catalytic performance of the supported PW4 catalysts was evaluated in H2O2-based oxidation of two model substrates, cyclooctene and methyl phenyl sulfide, under mild conditions (25-50 °C). The best results in terms of activity and selectivity were obtained using PW4 immobilized on N-free CNTs in acetonitrile or dimethyl carbonate as solvents. Catalysts PW4/CNTs can be applied for selective oxidation of a wide range of alkenes and thioethers provided a balance between activity and selectivity of the catalyst is tuned by a careful control of the amount of acid added during the immobilization of PW4. IR spectroscopy confirmed the retention of the Venturello structure after use in catalytic reactions. The elaborated catalysts are stable to metal leaching, show a truly heterogeneous nature of the catalysis, can be easily recovered by filtration, regenerated by washing and evacuation, and then reused several times without loss of the catalytic performance.